De Hou para Ozu : tessituras entre Taiwan e Japão em Café Lumière - Thiago Rodrigues Lima (2018)
This research investigates what Hou Hsiao-hsien addresses to Yasujiro Ozu in his work Café Lumière. Made in honor of the birth centenary of the Japanese director, the work mobilizes at the same time an update of the thematic universe of the Japanese director, focused on the daily life in the city of Tokyo, where traces of the history of Taiwan also orbit. Thus, we turn to Taiwanese history and cinema and to the comparison of their mise-en-scènes, observing the differences between them from the ideas of frame and flux, in order to probe into what Hou Hsiao-hsien offers to Yasujiro Ozu in contemporary times.